Germanium on silicon photodetectors with broad spectral range - Oehme, Michael; Kaschel, M.; Werner, J.; Kirfel, O.; Schmid, M.; Bahouchi, B.; Kasper, E.; Schulze, J. (Journal of The Electrochemical Society, 2010)
Vertical germanium on silicon p-i-n photodetectors were grown by molecular beam epitaxy and further processed by a quasi-planar mesa process. In this paper the influence of the n+ -top contact layer on the optical responsivity was investigated. The n+ -top contact was realized as highly antimony-doped silicon on a germanium heterostructure. With this additional heterostructure on top (relaxed silicon on relaxed germanium), the optical responsivity of the photodetector was broadened. The visible wavelength cutoff was shifted to 650 nm, whereas the long wavelength cutoff remained at 1550 nm. © 2009 The Electrochemical Society.
CRIS-Team Scopus Importer:2021-06-29